Malignant Lacrimal Sac Tumours—Review of the Literature and Report of Own Experience - Olga Karłowska-Bijak; Grażyna Stryjewska-Makuch; Marta Michalak-Kolarz; Magdalena Marków; Grażyna Lisowska (Medicina)
Background and Objectives: Tumours of the lacrimal drainage system are rare and most located in the lacrimal sac. The authors of this study aimed to conduct a literature review to find out which malignant tumours most often occurred in the lacrimal sac and what symptoms patients reported in the early stages of the disease. Materials and Methods: The PubMed database was searched for papers published between 2019 and 2024. The inclusion criteria were presence of an abstract, malignant lacrimal sac tumours, papers written in English, studies on humans, and case reports. The exclusion criteria were lack of an abstract, pathologies other than malignant tumours, including benign tumours of the lacrimal drainage system, malignant tumours of a part of the drainage system other than the lacrimal sac, papers in languages other than English, studies not involving humans, and no case report. No gender criterion was used. Results: Based on the data available in the literature, 31 studies were included in the article, describing 34 cases of malignant lacrimal sac tumours. Moreover, a case of a 58-year-old patient diagnosed with non-Hodgkin lymphoma was presented. Conclusions: As a result of the literature analysis, it was impossible to find any symptoms reported by patients with lacrimal sac tumours that would clearly suggest their diagnosis.